Conferences of the Karazin Institute of Environmental Sciences with the support of the Erasmus+ projects SUNRISE and DOMANI - HrechkoА. A.; Burchenko, S. V.; Kot, A. H. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2025)
Traditionally, three conferences were held at the Karazin Institute of Environmental Sciences in spring, namely: All-Ukrainian Student and Postgraduate English-language Conference “Ecology is a Priority”, IV International Internet Conference “Actual Problems of Formal and Non-Formal Education in Environmental Monitoring and Conservation” and ХХVII International conference «Ecology, environmental protection and balanced environmental management: Education – Science –Production – 2024». The conferences are devoted to the following topics: modern environmental problems and ways to solve them, applied environmental research, environmental consequences of the Russian-Ukrainian war and ways of post-war revitalization of natural complexes. In addition, much attention is paid to the problems and prospects of nature conservation in Ukraine and the world, environmental monitoring, and formal and informal education in environmental monitoring and conservation. The highlight of this year’s conferences was their holding under the auspices of two international projects: Erasmus + SUNRISE - Supporting the Next Generation of Ukrainian Scientists: Project to Enhance University Capacity and Improve Doctoral Training and DOMANI - Development of Microcredit Ecosystems in Ukraine and Mongolia for a Competitive and Sustainable Green Economy. The materials of all conferences were published in collections of abstracts, posted in the Karazin University repository, and participants received Certificates of Participation.